Inner pelvic measurements in dairy breeds - Szendrei, Zoltán; Holcvart, Mária; Elek, Sándor; Hódi, Katalin; Béri, Béla (Acta Agraria Debreceniensis, 2012)
Dystocia causes great financial losses: due to dystocia milk production is decreased and the probability of calf loss is increased. There are many factors that may cause dystocia. One of the factors –often investigated in beef cattle- is pelvic measurements. There have not been inner pelvic measurement comparisons in dairy breeds in Hungary. After comparing the imported, primiparous cows, Jersey turned out to have the smallest absolute inner pelvic measures. According to their age and weight, Brown Swiss cows had the largest pelvic dimensions. Ayrshires, Norwegian and Swedish Red, the three dairy breeds which share similar genetic background did not differ in most measures. Holsteins were closest to the seemingly ideal 1:1 horizontal and vertical diameter ratio; however this breed suffers the most from dystocia. Jerseys, despite having the smallest pelvic area are famous of their calving ease, perhaps not by coincidence. Though this dairy breed is the lightest, when pelvic area was compared in ratio of body weight Jerseys were not smaller than the 130 and 114 kg heavier Norwegian and Swedish Red cows.